Day-ahead and hour-ahead optimal scheduling for battery storage of renewable energy power stations participating in primary frequency regulation - Hu, Huaizhong; Ma, Yanzhao; Zhang, Xiaoke; Han, Chongshang; Hao, Yiran (Frontiers in Energy Research, 2024)
Due to the fast response characteristics of battery storage, many renewable energy power stations equip battery storage to participate in auxiliary frequency regulation services of the grid, especially primary frequency regulation (PFR). In order to make full use of the battery capacity and improve the overall revenue of the renewable energy station, a two-level optimal scheduling strategy for battery storage is proposed to provide primary frequency regulation and simultaneously arbitrage, according to the peak-valley electricity price. The energy storage output is composed of the droop-based primary frequency regulation output and the economic output, according to the electricity price. First, day-ahead optimization defines the economic output profile and an appropriate droop coefficient, considering regulation needs, with the goal of maximizing the overall return. The scheduling result is then adjusted for hour-ahead optimization based on the updated regulation information to ensure more durable and reliable performance. Simulation results show that the proposed scheduling strategy can fully utilize the battery capacity, realize peak-valley arbitrage while assuming the obligation of primary frequency regulation of the renewable energy power station, and then improve the overall income of the power station.